Reading Phinehas, watching slashers: horror theory and Numbers 25 - Grafius, Brandon R. (Lexington Books-Fortress Academic, 2018)
Keep it in the family -- History of Exegesis -- Numbers 25 and historical criticism -- Horror in theory -- Numbers 25 and horror theory -- Reading Phinehas